Essentialism and Racial Bias Jointly Contribute to the Categorization of Multiracial Individuals - Ho, Arnold K. (Psychol Sci, 2015)
Categorizations of multiracial individuals provide insight into the psychological mechanisms driving social stratification, but few studies have explored the interplay of cognitive and motivational underpinnings of these categorizations. In this paper, we integrate research on racial essentialism (i.e., the belief that race demarcates unobservable and immutable properties) and negativity bias (i.e., the tendency to weigh negative entities more heavily than positive entities) to explain why people might exhibit biases in the categorization of multiracial individuals. As theorized, racial essentialism, both dispositional (Study 1) and experimentally induced (Study 2), led to the categorization of Black-White multiracial individuals as Black, but only among individuals evaluating Black people more negatively than White people. These findings demonstrate how fundamental cognitive and motivational biases interact to influence the categorization of multiracial individuals.